Indication for CDKN2A-mutation analysis in familial pancreatic cancer families without melanomas. Issue 6 (25th May 2012) - Harinck, Femme; Kluijt, Irma; van der Stoep, Nienke; Oldenburg, Rogier A; Wagner, Anja; Aalfs, Cora M; Sijmons, Rolf H; Poley, Jan-Werner; Kuipers, Ernst J; Fockens, Paul; van Os, Theo A M; Bruno, Marco J
Abstract : Background: CDKN2A -mutation carriers run a high risk of developing melanomas and have an increased risk of developing pancreatic cancer (PC). Familial PC (FPC) patients with a personal history or family history of melanomas are therefore offered CDKN2A -mutation analysis. In contrast, CDKN2A testing in FPC families without a history of melanomas is not generally recommended. The aim of this study was to evaluate the frequency of CDKN2A -mutations in FPC families without melanomas. Methods: Data were gathered from PC family registers. FPC families were defined as families with clustering of PC without meeting diagnostic criteria of familial cutaneous malignant melanoma (familial CMM) or other inherited cancer syndromes. Blood samples were obtained for DNA isolation from PC patients or first degree relatives and analysed for CDKN2A -mutations. Results: Among 40 FPC families, DNA analyses were carried out in 28 families (70%), leading to identification of CDKN2A -mutations in six families (21%). None of the CDKN2A -mutation-positive families fulfilled the diagnostic criteria for familial CMM and in three CDKN2A families no melanomas were observed. Two CDKN2A -mutations were found; the Dutch founder mutation p16-Leiden (c.225_243del, p.Ala76fs) and the c.19_23dup, p.Ser8fs-mutation. After disclosure of the CDKN2A -mutation in one of the families, a curable melanoma was diagnosed at dermatological surveillance in a 17-year-old family member. Conclusion: CDKN2A -mutation can be found in a considerable proportion of families with FPC. CDKN2A -mutation analysis should therefore be included in genetic testing in FPC families, even in the absence of reported melanomas. This strategy will enhance the recognition of individuals at risk for PC and facilitate the early detection of melanomas.